Vitamin D and Cardiovascular Disease: An Appraisal of the Evidence - Schnatz, Peter F. (2013)
BACKGROUND: Supplementation with vitamin D (VitD) has received attention as a potential cardioprotective strategy. Biologically plausible mechanisms have been proposed to link VitD to coronary heart disease (CHD) prevention and observational studies suggest an inverse association between serum 25-hydroxyvitamin D (25OHD) concentrations and CHD. Few randomized clinical trials of VitD supplementation and CHD have been conducted, however, and no completed trial has been done with CHD as the primary pre-specified outcome. CONTENT: A search was conducted in PubMed to find prospective studies on the use of vitamin D supplementation and cardiovascular risk factors (RFs) and/or cardiovascular disease. The exact search query was ((vitamin D supplement*[Title/Abstract]) AND cardiovascular [Title/Abstract]) AND prospective [Title/Abstract]. This query yielded 42 results. Randomized Controlled Trial (article type) was employed as a filter in a subsequent query with the same search terms. We review the evidence that VitD supplementation modifies coronary RFs, such as blood pressure, lipids, and glucose tolerance, and/or affects the development of clinical CHD events. We address potential sources of confounding in observational epidemiologic studies of the relationship between serum 25OHD and CHD. We also address laboratory assay issues relevant to the reliable measurement of 25OHD. SUMMARY: Most VitD supplementation trials have not demonstrated improvement in cardiovascular disease, but have tested relatively low doses of VitD. Thus, the evidence remains inconclusive, highlighting the need for rigorous randomized trials of higher VitD doses, with cardiovascular events as prespecified outcomes. While awaiting ongoing trial results, the recommended dietary allowances from the Institute of Medicine remain the best guidepost for nutritional requirements.